The Effects of Pretreatment with Achillea santolina and Stachys athorecalyx Extracts on CFA-induced acute inflammation in male rats - E Tekieh; Sh Rezazadeh; H Manaheji; A Akbari; J Zaringhalam (Institue of Medicinal Plants, ACECR, 2010)
Background: Inflammatory symptoms, hyperalgesia and edema, as a physiologic responses for stimulus can mediate via different mediators such as cytokines. Medicinal plants are an important source of substances which are claimed to induce anti-inflammatory effects. Objective: Regarding to these and on account of the Interlukine-6 roles in hyperalgesia and edema induction, the aim of this study explained to investigation of the pre-treatment effects of Achillea santolina and Stachys athorecalyx extracts on inflammation which induced by CFA in male Wistar rats. Methods: Methanolic and defatted extractions were done on aerial parts of the both plants: Achillea santolina and Stachys athorecalyx. 50, 100 and 200 mg/kg doses of extracts were selected for treatment. Results: Results indicated that pre-treatment with defatted and methanolic extracts of S. athorecalyx significantly decrease CFA-induced hyperalgesia and edema dose-dependently. At same situation only methanolic extract of A. santolina was effective in inflammatory signs reduction. Conclusion: It can concluded that A. santolina and S. athorecalyx extracts can be effective candidate for pre-treatment of inflammation, but the effective substances of them are different and need to be more investiged.